Case Report on Amoxiclav induced Steven Johnson’s Syndrome with Medium Vessela Vasculitis - Ray, Pravin Kumar; Maheswari, Nelli; Basnet, Subarna; Gupta, Mukesh Kumar (Indian Journal of Pharmacy Practice)
Stevens-Johnson Syndrome (SJS) is a rare and serious medical emergency that affects the skin and mucous membranes. It is typically caused by an adverse reaction to medication or infection, resulting in an immune system response that causes inflammation and destruction of skin cells occur at any age. We present the case study of 46-year-old female patient who develop an erythematous maculopapular lesion on 3rd day of using antibiotic (amoxiclav). Diagnosis of SJS is typically based on clinical presentation and a skin biopsy. In this cases, blood tests and cultures have been done to rule out infection as the cause of symptoms. Symptoms of SJS can include fever, cough, sore throat, and a painful rash that can blister and peel. In severe cases, SJS can cause damage to internal organs and be life-threatening. Treatment typically involves discontinuing the offending medication and providing supportive care, such as pain relief and wound care. Prevention of SJS involves avoiding known triggers and carefully monitoring medication use.
Keywords: Erythematous; SJS; Amoxiclav